2019
DOI: 10.5851/kosfa.2019.e74
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture and Physicochemical Properties of Chitosan Oligosaccharide/A2 β-Casein Nano-Delivery System Entrapped with Resveratrol

Abstract: The purposes of this research were to form chitosan oligosaccharide (CSO)/A2 β-casein nano-delivery systems (NDSs) and to investigate the effects of production variables, such as CSO concentration levels (0.1%, 0.2%, and 0.3%, w/v) and manufacturing temperature (5°C, 20°C, and 35°C), on the production and physicochemical characteristics of CSO/A2 β-casein NDSs to carry resveratrol. The morphological characteristics of CSO/A2 β-casein NDSs were assessed by the use of transmission electron microscopy (TEM) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the binding of hydrophobic resveratrol to the caprine casein/polysorbate-20 complex is likely to be driven by interaction with caprine β-casein. A recent study showed that resveratrol was less susceptible to degradation when entrapped in A2 β-casein from caprine milk and chitosan oligosaccharide [ 50 ]. In agreement with these findings, the results of our study implied a possible correlation between caprine β-casein functionality and the stability of resveratrol.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the binding of hydrophobic resveratrol to the caprine casein/polysorbate-20 complex is likely to be driven by interaction with caprine β-casein. A recent study showed that resveratrol was less susceptible to degradation when entrapped in A2 β-casein from caprine milk and chitosan oligosaccharide [ 50 ]. In agreement with these findings, the results of our study implied a possible correlation between caprine β-casein functionality and the stability of resveratrol.…”
Section: Resultsmentioning
confidence: 99%
“…High concentration of β‐casein (0.5–2.0 mg/mL) is able to encapsulate some water‐insoluble drugs (Zimet et al., 2011), such as fat‐soluble vitamins and polyunsaturated fatty acids, inside by self‐assembling to form micelles, which shows high encapsulation efficiency and significant degradation protection (Li, Auty, et al., 2019; Ranadheera et al., 2016; Wei et al., 2018). These results may be useful for the development of biologically active natural carriers based on β‐casein (Kim et al., 2019; Perinelli et al., 2019).…”
Section: Application Of β‐ and β‐Casein‐depleted Casein Concentrate B...mentioning
confidence: 99%